Recruitment of monocytes/macrophages by tissue factor-mediated coagulation is essential for metastatic cell survival and premetastatic niche establishment in mice. - Gil-Bernabé, A; Ferjancic, S; Tlalka, M; Zhao, L; Allen, P; Im, J; Watson, K; Hill, S; Amirkhosravi, A; Francis, J; Pollard, J; Ruf, W; et al. (American Society of Hematology, 2012)
Tissue factor (TF) expression by tumor cells correlates with metastasis clinically and supports metastasis in experimental settings. However, the precise pathways coupling TF to malignancy remain incompletely defined. Here, we show that clot formation by TF indirectly enhances tumor cell survival after arrest in the lung, during experimental lung metastasis, by recruiting macrophages characterized by CD11b, CD68, F4/80, and CX(3)CR1 (but not CD11c) expression. Genetic or pharmacologic inhibition of coagulation, by either induction of TF pathway inhibitor ex-pression or by treatment with hirudin, respectively, abrogated macrophage recruitment and tumor cell survival. Furthermore, impairment of macrophage function, in either Mac1-deficient mice or in CD11b-diphtheria toxin receptor mice in which CD11b-positive cells were ablated, decreased tumor cell survival without altering clot formation, demonstrating that the recruitment of functional macrophages was essential for tumor cell survival. This effect was independent of NK cells. Moreover, a similar population of macrophages was also recruited to the lung during the formation of a premetastatic niche. Anticoagulation inhibited their accumulation and prevented the enhanced metastasis associated with the formation of the niche. Our study, for the first time, links TF induced coagulation to macrophage recruitment in the metastatic process.